Pattern of muscular activity in the trunk, thigh and lower leg during the underwater dolphin kick in elite female competitive swimmers - Kobayashi, K.; Shimojo, H.; Takagi, H.; Tsubakimoto, S.; Sengoku, Y. (Japan Journal of Physical Education, Health and Sport Sciences, 2016)
The purpose of this study was to clarify the pattern of muscular activity in the trunk, thigh and lower leg during the underwater dolphin kick in elite female competitive swimmers. The participants were 9 national-level competitive female swimmers who performed underwater dolphin kick swimming for 15 m at maximum effort. Sagittal movement was recorded for 2-D motion analysis, and surface electromyographic (EMG) data were recorded from six muscles: rectus abdominis (RA), elector spinae (ES), rectus femoris (RF), biceps femoris (BF), tibialis anterior (TA), and gastrocnemius (GAS). The EMG data were used to investigate the active phase during one kick cycle. Furthermore, the co-active phases between the agonist and the antagonist in the trunk, thigh and lower leg were evaluated in terms of estimated muscular coordination. The kinematic results indicated that the average swimming velocity and the strouhal number for these swimmers were similar to those for Olympic swimmers in a previous study. Furthermore, a whiplash-like action was observed in their underwater dolphin kick movement. The EMG results indicated that the active phases of all subjective muscles during one kick cycle were approximately 60%. Co-active phases were observed in all pairs (RA-ES: 24.1±10.1%, RF-BF: 23.2±5.5%, TA-GAS: 45.5±20.2%), and the co-active phase of TA-GAS was significantly larger than for the other pairs (p<0.05). From these results, two main findings emerged with regard to the muscular activity pattern during the underwater dolphin kick in elite female competitive swimmers: (1) the muscular activity patterns in the trunk and thigh muscles were reciprocal; (2) the co-active phase for the lower leg muscles was larger than for the other parts and occurred during the first half of the upward kick phase.